Knowledge about first aid among physical education professionals outside school settings - Silva, Vitor Loureiro da; Nunes, Régis de Lirio; Pereira, Camila Cristina Adeodato; Lima-Leopoldo, Ana Paula; Lunz, Wellington; Vancini, Rodrigo Luiz; Leopoldo, André Soares (Revista Sustinere, 2022)
Approaches of Physical Education professionals, which work in non-school settings, include the development of simple physical activities for health maintenance and quality of life improvement, physical training prescriptions for high performance purposes and orientation of therapeutic protocols. However, the interventions may lead to accidents of all types to the practitioners and, therefore, it obliges the professionals to act as a primary rescuer in situations of urgency and emergency. This research aimed to investigate the knowledge level in first aid of Physical Education professionals who work in non-school settings. Three hundred eighteen Physical Education professionals, who work non-school settings, were submitted to questionnaires with multiple choices, and essay questions about First Aid. The participants, on a larger scale, had access to First Aid contents during the academic education period, either at college or through external courses (92.8%). However, the course completion, at a specific time in the undergraduate process, has not been sufficient to prepare them for urgency and/or emergency situations. In addition, they presented little ability with basic concepts and behaviors, especially regarding cardiopulmonary resuscitation and the use of automatic external defibrillator. Additionally, 72% of professionals answered they do not have self-confidence to provide first aid in any situation. In conclusion, Physical Education professionals present insufficient theoretical knowledge in first aid, being necessary some better training in this area, both in the theoretical and practical aspects.